Performance Improvement for Wireless Mesh Networks with Renewable Energy Source - Sun, Peng (Université d'Ottawa / University of Ottawa, 2016)
Multi-radio multi-channel wireless mesh networks (WMNs) have been the focus of numerous research efforts during the past few years. These efforts aimed at extending the utilization of technologies based on the IEEE 802.11 standard in large-scale communities and even for city wide networking. However, mesh nodes in these networks are typically limited in their resources (e.g., bandwidth, power and radio interfaces). Such a limitation has led to an unsatisfactory network performance as well as users dissatisfaction. This dissertation addresses three important performance issues related to WMNs, namely, network performance enhancement, network survivability and green communications. To address the first issue, a novel quality of service (QoS) aware joint channel assignment (CA) and routing algorithm is developed. The proposed algorithm employs both dynamic and static CA techniques and corresponding link schedules that maximize the network throughput and minimize the delay and packet loss ratio. Next, the thesis addresses the problem of network survivability and theoretically analyzes the effects of node failure probabilities on the ability of the remaining network nodes to maintain their connectivity. A tight upper bound on the node failure probabilities needed to maintain full network connectivity on the one hand is first developed. On the other hand, a lower bound, at which the system loses connectivity, is also derived. We show that these bounds are dependent only on the nodes' geometric distribution and density. Based on the premise that failure of nodes in a small area may lead to failure of dependent nodes in other areas due to the quick divergence of traffic in these areas, an efficient node failure backup scheme is presented. The scheme relies on the capacity of the surviving network components in order to find new paths that do not overload the neighbours of the failed node which reduces the probability of generating congestion. Finally, the thesis addresses the problem of realizing energy-efficient WMNs that can operate using renewable energy sources. In these systems, batteries are often used to store and regulate the use of the supplied green energy to transmit the received data at each network router in order to overcome the problem of supply fluctuating of various energy sources. To realize these networks, the behaviour of the residual energy of the battery at a heavily loaded green wireless mesh node with a general traffic arrival and energy charging functions is first analyzed. Based on obtained theoretical results, both an online and an offline QoS aware packet scheduling schemes are proposed to minimize the probability of depleting the battery. Each of the aforementioned contributions is supported with various experimental evaluations to demonstrate the achieved performance enhancements.
Keywords: Wireless Mesh Networks; Survivability; Energy efficiency; Renewable Energy; Backup scheme; Green communication